Ideological Contestation of Islamic Organisations in Indonesia: A Case Study of Muhammadyah and Nahdlatul Ulama - Rohman, Alif Nur; Assaiq, Muhammad Royhan; Ulfah, Mailani; Sudi, Ahmad; Siswanto, Siswanto; Wijaya, Roma (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
This article discusses the ideological contestation between Muhammadiyah and Nahdlatul Ulama (NU), where Muhammadiyah was established in the early 20th century. The birth of the two mass organisations is inseparable from the influence of thought that developed in the Islamic world at that time, which has implications for the ideological differences between the two. Therefore, this research specifically examines the characteristics of ideological contestation between Muhammadiyah and NU. This research is a qualitative literature study that collects data from various documents, such as books, journal articles, and other sources. The ideology that becomes the material object in this research is then analysed using the theory of ideological contestation. This theory will reveal four characteristics of contestation, namely: variations in different norms, two modes of contestation, three stages of norm implementation, and four cycles of validation. This research shows that differences in basic norms, modes of contestation, and norm implementation are the main drivers of the dynamics between Muhammadiyah and NU. The ideological contestation between Muhammadiyah and Nahdlatul Ulama (NU) is reflected in their different approaches to religious norms, where Muhammadiyah emphasises purification of Islamic teachings through the establishment of modern institutions such as schools and hospitals, while NU adapts local traditions through pesantren that integrate traditional religious values. Their validation also differs, with Muhammadiyah gaining formal recognition from the colonial government, while NU gains strong cultural legitimacy in rural communities through deep-rooted religious ritual traditions. This contestation not only shaped the socio-political identity of Muslims in Indonesia, but also contributed to the formation of a national identity rich in religious and cultural values.